Escalating Student's Speaking Skills Through The Employment of VoA Learning English Videos - Liana, Hafifah; Aminatun, Dyah (Jurnal Riset dan Inovasi Pembelajaran, 2025)
This study explores the effectiveness of using VOA Learning English videos to improve students' speaking skills. By integrating authentic audiovisual materials from VOA, this study demonstrated significant improvements in students' confidence, fluency and expressive skills in spoken English. This study use a quasi-experimental design as the research methodology. The sample of this study included the experimental class XI IPS 1 and the control class XI IPS 2 at SMA Negeri 1 Penengahan. The findings highlight the potential of multimedia resources to actively engage students and facilitate practical language use. This approach offers valuable insights for educators seeking effective strategies to improve speaking proficiency, emphasizing the role of external media resources in language teaching. This research contributes to the field of English language learning by providing evidence that VOA videos can be a powerful tool to encourage active participation and skill development in speaking activities.